Generalized Gribov-Lipatov Reciprocity and AdS/CFT. (30th June 2010) - Beccaria, Matteo; Forini, Valentina; Macorini, Guido
Abstract : Planar𝒩 = 4 SYM theory and QCD share the gluon sector, suggesting the investigation of Gribov-Lipatov reciprocity in the supersymmetric theory. Since the AdS/CFT correspondence links𝒩 = 4 SYM and superstring dynamics onA d S 5 × S 5, reciprocity is also expected to show up in the quantum corrected energies of certain classical string configurations dual to gauge theory twist-operators. We review recent results confirming this picture and revisiting the old idea of Gribov-Lipatov reciprocity as a modern theoretical tool useful for the study of open problems in AdS/CFT.